APLIKASI TAGIHAN REKENING AIR BERBASIS SMS GATEWAY PADA PDAM KOTA SEMARANG (Information Technology and Telematics, 2015)
Abstract : Information technology is growing rapidly. database becomes a major requirement for support information on all companies. in addition serves to store information, data bases can also be used to process the data as needed. In the midst of technological developments, also required a reliable application which has the consistency and integrity of data. In this case, the security of data storage requires special attention in order to keep the quality is guaranteed. Regional Water Company (PDAM) Semarang is one of the areas that is always trying to improve the quality of service to its customers. In this case will provide information check water bill based short massages service (SMS) to facilitate customers in knowing the monthly water bill. Keywords : Account Billing Applications, SMS gateway, PDAM city Semarang.